The Sayfahs of the Translation and Tafseer of the Noble Qur’an Into Albanian Language - İsmail Bardhi (Yakın Doğu Üniversitesi İlahiyat Fakültesi Dergisi)
This paper, namely The Sayfahs of Translation and Tafseer of theQur’an al-Kareem into Albanian Language, is divided in three parts:Political and Cultural-Religious Circumstances; Translations of theQur’an into Albanian Language; and The Tradition of the Tafseer ofthe Qur’an among Albanians.The first part deals with the difficult times that have prevented thedevelopment of religious culture, not only by hindering this culture,but also by impoverishing, destroying and throwing it into oblivion,and that historical period left consequences for the future too.Translations of the Qur’an have overcome that difficult phase, andAlbanian Muslims with a particular care and love began the partialand latter the complete translation of God’s Word. Regarding theissue of translation one may notice important debates in Muslimintellectual and institutional circles. Of course, at the beginningonly partial translations were done and published, and much latterthe complete ones. Also, in this part names of the translators of theQur’an into Albanian language are presented.The tafseer tradition is presented in detail, beginning with thenames of of mufassirs up to the sayfahs of their tafseers, partial andcomplete – systematic. The ways of dealing with the subjects by Albanianmufassirs show the influence of various schools of tafseer,that of the Ottoman Empire, the Arab and the Albanian religiousschool. Sources that prove the aforementioned are also given.In this work mainly the literature of the Albanian people writtenin their own language has been used, intending to make that literaturea part of the literature of the tafseer of the Qur’an as well asto present the tireless work and efforts of Albanian Muslim translatorsand mufassirs.